An attempt to measure force and moment acting on hub-bearing with ultrasonic technique - Akitoshi TAKEUCHI (Nihon Kikai Gakkai ronbunshu, 2018)
Ultrasonic pulse reflection method was employed for in situ estimation of several forces including moment acting on dual race type hub-bearing operating with low speed. The estimation of these forces was performed through the observation of echo height h which is reflected from the interface of outer ring/ball and varied with contact condition of lubrication surface. The echo ratio H (=h/h0 : h0 is the echo height in dry condition) is decreased at the ball position in loading side (dense contact) and is increased in unloading side (sparse contact). For instance, the reflection echo height h in upper side of hub bearing is decreased, since the supporting load of the ball in there increases, when only the load (vertical force) Fz is applied to the bearing through the tire. Meanwhile, the echo height in lower side of the bearing is increased up to the quantity same as the variation mentioned above in contrast to upper side, because the supporting load of the ball in lower side is decreased. The behavior of such contrastive H appears, when the axial force, the moment around x-axis horizontal to the roadbed and the moment around z-axis vertical to the roadbed are applied to bearing. Estimation of the load and the axial force becomes possible from the mean value of the echo ratio change that those contrastive influences in H are canceled. Moreover, the estimation of the moment around x or z-axis is enabled from the differences between such mean value and echo ratio change of each ball. Then, the potential that can individually measure the several forces and moments generated by steering was clarified, even if the condition that they were superimposed simultaneously.